Pengembangan Aplikasi Stok Barang Berbasis Web Menggunakan HTML - Ahmed Hendra Widjoyo; Ara Dwi Nata; Arya Kusuma Wardhana; Rama Andika; Aries Saifudin (CV. Multi Kreasi Media, 2024)
One of the main problems that can arise in web-based inventory applications is the problem of application development, because if the system is inadequate or not protected properly, important data such as stock information, transactions, and customer details can be vulnerable to hacker attacks or data theft. To overcome problems that may arise in web-based inventory applications by conducting regular monitoring of the stock application system. Ensure monitoring includes system availability, performance, and data integrity. Also, back up data regularly to avoid losing important information due to hardware failure or hacker attacks. Make sure data backups are stored in a safe place and can be accessed if needed. The application of this method to the problem of web-based inventory applications can provide several positive results, including stock management efficiency: By using the right method, the application of stock items can help improve stock management efficiency. Methods such as the Just-in-Time (JIT) or EOQ (Economic Order Quantity) methods can help companies to manage purchasing and shipping goods more efficiently, avoiding overstock or stock shortages that can hinder operations.